Monitoring and prevention of overtraining in athletes - Nascimento Alves, R.; Oliveira Pena Costa, L.; Samulski, D. M. (Revista Brasileira de Medicina do Esporte, 2006)
Overtraining is characterized by the imbalance between stress and recovery. Besides that, stress factors can be found not only in situations of training and competition, but also in extra-training and extra-competition ones. The athletes, in the attempt of reaching high performance levels with training, can become excessively trained, showing signs and symptoms of overtraining. Overtraining can be identified through symptoms like underperformance, chronic fatigue, respiratory infections and mood swings. Although there is no indication that overtraining causes irreversible damage to the athlete, the risk of injury, diseases or drop-out of sport is increased, reducing athletes` life quality. Based on these considerations, parameters and instruments for monitoring and prevention in physiological and psychological fields are studied in this work. Therefore, the best strategy for monitoring is to associate psychological parameters with physiological evaluations. Concerning prevention and treatment of overtraining, the implantation of systematized program of prevention of harmful effects in the athlete`s performance, in his health and consequently in his well-being is advisable.